Immunological Effects of Chitosan Nanoparticles on Breast Cancer Cells in Animal Model - Neda Soleimani; Ashraf Mohabati Mobarez (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2017)
Background and Objectives: Cancer is one of the leading causes of death around the world with a very high degree of mortality. Conventional therapies by cytotoxic drugs have high levels of side-effects for patient. Chitosan is a biocompatible and biodegradable compound. Thus, according to the minimum systemic toxicity for peptide and drug delivery, it is considered in applied programs. In this study, the Immunological effect of chitosan nanoparticles, was investigated on breast cancer cells in animal model.